Die verband tussen ekklesiologie en kerkreg: "n Hervormde perspektief - Wyk, Barry J. van (HTS teologiese studies, 2017)
This article discusses the meaning of ecclesiology and church polity as such, in relation to each other, but also in connection to church order which lies in the elongation of both. From a reformed perspective, it is indicated that the ecclesiology of the Netherdutch Reformed Church over the last fifty to hundred years, centred round the viewpoint of the Church as a volkskerk, in conjunction with the church orderly, of the Kerkwet till 1997. The author is of the opinion that the above-mentioned viewpoint limited the church to be a true church of the Word.